Health care in the European Union – organization and functioning of health care systems - Tatara, Tomasz; Matysiak, Agata; Wyrozębska, Agnieszka (Polish Journal of Public Health, 2009)
All of European health systems show some similarities with regard to legal, organizational and fi nancial issues, as well as how the system and its features are running. It is worth to mention that none of the European Union members has accepted common healthcare system policy. Key EU treaties including Maastricht Treaty (1992) and Amsterdam Treaty (1997) do not impose an obligation to do so. Main stipulations say: „The European Community will act in a way of securing high level of healthcare protection” and “High level of healthcare protection will be taken into account in development and implementation of European Community’s policies and activities”. Other stipulations in above mentioned treaties undoubtedly show no intention to intervene in organization and functioning within members’ healthcare systems. Therefore diversity of adopted solutions has been granted. The course of European Communities policy is to develop common standards and rules of healthcare systems with regard to public welfare as the biggest asset of each nation. This paper presents two main models that most of worlds healthcare systems are based on. Those models give background for the comparison of various healthcare systems run in the European Union.